Lékari primární zdravotní péce v Ceské republice z pohledu demografie--soucasný stav jako zakládní kámen budoucího vývoje - Sídlo, Ludek (Casopis lekaru ceskych, 2010)
The number of primary health care physicians in the Czech Republic in recent years has been relatively stable. Nothing indicates that already in a few years there could be considerable problems in terms of quality and accessibility of primary health care. The reason for this assertion is the irregular age structure of the particular branches of this type of care, where a significant number of physicians is concentrated in the age range of 50-60 years. There is currently no adequate substitute for physicians in the form of young doctors; problems will not be solved even by the possible influx of physicians from abroad. After leaving of the strong generation of physicians from primary health care, especially to retirement, there is a risk of collapse, especially in branches of the practical medicine for children and youth and general practical medicine. Future development of the negative number and structure of physicians in primary health sector is an irreversible process, which could be currently eliminated only by the quick action of the authorities involved--the relevant ministries, health insurance companies and/or professional associations.
Keywords: Česká republika; Physicians, Primary Care; Middle Aged; mužské pohlaví; ženské pohlaví; Humans; lékaři primární péče; Population Dynamics; Female; populační dynamika; Czech Republic; lidé; Male; lidé středního věku